Patogen Pembawa Penyakit Staphylococcus aureus dan Prevalensinya pada Pangan Hasil Pertanian - Erliana Novitasari; Danarsi Diptaningsari (Jurnal Riset Agribisnis dan Peternakan, 2022)
Pathogen contamination of foods might cause infectious diseases called foodborne illnesses. Generally, infection is caused by a pathogen, virus, or parasite through contaminated food ingestion. Staphylococcus aureus is one of the most common foodborne pathogens causing infection in the world which is included in the gram-positive bacteria. The growth and survival of S. aureus are dependent on a number of environmental factors such as temperature, water activity (aw), pH, the presence of oxygen, and the composition of the food. Symptoms that arise due to S. aureus bacterial infection include high fever, vomiting, and diarrhea. Many studies have reported the incidence of S. aureus contamination of agricultural food products, for example, meat, dairy products, fish, and even vegetables.